People Recruitment Model for Effective and Sustainable Mosque Management - Andri Ansyah, Rahmat Husein (Proceedings of International Conference on Da'wa and Communication, 2019)
Mosque has a pivotal role for da’wa and muslim community development. Unfortunately many of them have lost such functions nowadays and the caretaker is among the main reasons: an active board of caretaker results an active mosque and vice versa. Thus, a model of effective and sustainable people recruitment is needed for mosque to be optimally functional. This research analyzes two longlasting mosques in Surabaya, Al-Falah and Al-Abror, to develop the model. Al-Falah is a downtown mosque while Al-Abror is located in a suburban area. Both are regarded as sustainable mosques due to their ability and consistency in performing community development through their programs and people management in more than 40 years of their existence. The objective of this grounded research is to understand the people recruitment planned and implemented by both mosques’ board of caretaker. Using in-depth interview and inductive analysis, this research reveals three important points of findings. Firstly, strategic value proposition in mosque people recruitment consists of mosque organizational vision, work-related spiritualism, personal track record allignment and material incentive. Secondly, although recruitment source primarily is from internal (within recent or previous board of caretaker), external source (people from any background and residential area) is proven to be effective. Last, personal and word of mouth through social media platform such as WhatsApp are the preferred method for recruitment.